"Fiktion" und "Wirklichkeit" in japanischen Literaturtheorien der Jahre 1850 bis 1890 - Woldering, Guido (Welten Ostasiens / Worlds of East Asia / Mondes de l'Extrême Orient, 2022)
Which relationship should, must, or can creation in language (fiction) have to creation outside of language (reality)? How do theoretical notions of literary art change when reality drastically changes? This volume investigates these questions in relation to the literature and social history of Japan from 1850 to 1890.